Clinical Implications In Pyle`s Disease, (Familial Metapyseal Dysplasia), Report Of Five Cases with Review Of The Literature. - Kitab, Sameer A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Pyle`s disease is a distinct skeletal dysplasia with defective metaphyseal modeling and Erlenmeyer-flask deformity of tubular bones.Objectives: Clinical implications in five reported cases with mechanical bone properties different from normal bones were presented. One patient with Genu-valgum deformity had corrective osteotomy done with internal fixation showing osteotomy healing and sustained deformity correction with more than twelve years of follow up. Two patients presented with fractures and angular malalignment with abundant callus .The other two had insufficiency fractures due to repetitive low energy activities.Results: Patients with Pyle`s disease have less than normal mechanical bone properties, insufficiency fracture or gross fractures may develop after low energy or repetitive trauma. Internal fixation can be used and healing may progress with abundant callus.Conclusions: Pyle`s disease stands as a distinct type of metapyseal dysplasia with characteristic clinicalradiological criteria.Genu valgum deformity may warrant osteotomy correction, Internal Fixation can be used and osteotomy may be rapid to heal with the widened bone surfaces. Protection against potential angular malalignment is important until there is sound healing of the fractured bone. Because of increased fragility of bone, a word of caution may be appropriate in the young patient indulged with sports activity.